Perlindungan Konsumen dalam Perjanjian Jual Beli Condotel dengan Sistem Pre-Project Selling - Aang Gunafi; Niru Anita Sinaga (LOCUS MEDIA PUBLISHING, 2025)
This study discusses the validity of the Sales and Purchase Agreement (PPJB) in condotel transactions marketed using a pre-project selling system, as well as the form of legal protection for buyers in the event of default by the developer. The increasingly widespread practice of pre-project selling in Indonesia often gives rise to legal problems due to the potential for default due to developers not fulfilling their obligations under the agreement. This is exacerbated by the weak bargaining position of buyers due to the PPJB being unilaterally drafted as a standard agreement. The research method used is normative juridical with a statutory approach and case studies. Data are reviewed based on the Civil Code (KUH Perdata), Law Number 20 of 2011 concerning Apartments, and Law Number 8 of 1999 concerning Consumer Protection. The results of the study indicate that PPJB is legally valid if it meets the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. However, its implementation is often unbalanced and ignores the principle of justice. Legal protection for buyers can be achieved through preventive and repressive channels, including demanding fulfillment of agreements, cancellations, and compensation.